1986
DOI: 10.1007/bf00290537
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical safety testing of species-specific proteins produced with recombinant DNA-technqiues

Abstract: Preclinical toxicity studies in animals with species-specific recombinant DNA products have now been performed for several years. An interim statement on the significance of these animal tests and their ability to predict adverse effects in humans therefore appears indicated, with the aim of deducing future testing strategies. The experience accumulated so far shows that the animal models have failed to predict adverse effects subsequently observed in man. Immunogenicity of these proteins further restricted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The desired pharmacologic effects were not being obtained in the usual animal species employed in small molecule toxicology studies, and to make matters more complicated, immunological responses including production of neutralizing antibodies to the foreign proteins were being mounted within the time frames of the usual toxicology study. It was also observed that the results of nonclinical testing of species-specific proteins in animal studies did not adequately predict adverse effects later observed in the patient population because of the use of pharmacologically nonrelevant animal species and/or the development of anti-drug antibodies (Teelmann et al, 1986). Therefore, it was apparent at the outset that nonclinical safety testing of biotechnologyderived pharmaceuticals was going to be conducted on a caseby-case basis, with selection of the tests required being driven by such factors as the nature of the production cell substrate (bacterial or mammalian cell type used), the type of product (monoclonal antibody, recombinant protein, cellular vaccine, etc.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The desired pharmacologic effects were not being obtained in the usual animal species employed in small molecule toxicology studies, and to make matters more complicated, immunological responses including production of neutralizing antibodies to the foreign proteins were being mounted within the time frames of the usual toxicology study. It was also observed that the results of nonclinical testing of species-specific proteins in animal studies did not adequately predict adverse effects later observed in the patient population because of the use of pharmacologically nonrelevant animal species and/or the development of anti-drug antibodies (Teelmann et al, 1986). Therefore, it was apparent at the outset that nonclinical safety testing of biotechnologyderived pharmaceuticals was going to be conducted on a caseby-case basis, with selection of the tests required being driven by such factors as the nature of the production cell substrate (bacterial or mammalian cell type used), the type of product (monoclonal antibody, recombinant protein, cellular vaccine, etc.…”
Section: Introductionmentioning
confidence: 93%
“…One outstanding issue that became apparent early on was that many of the recombinant proteins were highly species-specific, and selection of the appropriate animal models for predicting efficacy and target organ toxicity was going to be problematic because of lack of pharmacologic activity of proteins among various animal species due to structural (e.g. amino acid sequence) differences (Teelmann et al, 1986). The desired pharmacologic effects were not being obtained in the usual animal species employed in small molecule toxicology studies, and to make matters more complicated, immunological responses including production of neutralizing antibodies to the foreign proteins were being mounted within the time frames of the usual toxicology study.…”
Section: Introductionmentioning
confidence: 99%
“…When the first biopharmaceuticals entered the market, it was already clear that the value of animal experimentation in the preclinical safety evaluation of biopharmaceuticals was limited due to species specificity and immunogenicity [1,3,5,16]. At the same time, the European Union expressed its ambition to reduce animal experimentation in Directive 86/609/EEC.…”
Section: The Risk Of Risk Aversionmentioning
confidence: 99%
“…At that time it was already known that the classical preclinical safety evaluation procedure applied to small molecule therapeutics (SMTs) would not predict adverse effects of biopharmaceuticals [1]. The checkbox approaches used in the classical procedure were considered not appropriate [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation